2005
DOI: 10.1007/bf02898612
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic theory of inverse beta-decay of polarized neutron in strong magnetic field

Abstract: The relativistic theory of the inverse beta-decay of polarized neutron, ν e +n → p+e − , in strong magnetic field is developed. For the proton wave function we use the exact solution of the Dirac equation in the magnetic filed that enables us to account exactly for effects of the proton momentum quantization in the magnetic field and also for the proton recoil motion. The effect of nucleons anomalous magnetic moments in strong magnetic fields is also discussed. We examine the cross section for different energi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
0
7
0
6
Order By: Relevance
“…Similarly to the pion decay rate, the magnetic field will have an impact on (inverse) β-decay rates and nucleon electroweak transition form-factors. Indeed, an enhancement by the magnetic field is expected for processes involving nucleons as well [40][41][42], see, e.g., the review [43]. The tools developed in the present letter will also be useful to study these effects that are relevant for cold and magnetized environments.…”
mentioning
confidence: 81%
“…Similarly to the pion decay rate, the magnetic field will have an impact on (inverse) β-decay rates and nucleon electroweak transition form-factors. Indeed, an enhancement by the magnetic field is expected for processes involving nucleons as well [40][41][42], see, e.g., the review [43]. The tools developed in the present letter will also be useful to study these effects that are relevant for cold and magnetized environments.…”
mentioning
confidence: 81%
“…Note that the same asymmetry appears in case of much stronger magnetic fields B > B cr as well as for other similar processes (6.94). Recently the relativistic approach to the inverse β decay of a polarized neutron, ν e + n → p + e − , in a magnetic field has been developed by Shinkevich and Studenikin (2005) 17 . It was shown that in strong magnetic fields the cross section can be highly anisotropic with respect to the neutrino angle.…”
Section: Beta Decay Of the Neutron In A Magnetic Fieldmentioning
confidence: 99%
“…We recall also different other mechanisms for the asymmetry in the neutrino emission from a magnetized pulsar studied by Kusenko and Segre (1996); Bisnovatyi-Kogan (1993); Akhmedov et al (1997); Lai and Qian (1998). For more complete references to the performed studies on the neutrino mechanisms of the pulsar kicks see the introductions presented by Bhattacharya and Pal (2004); Shinkevich and Studenikin (2005). Presently there is no solid explanation of the observed pulsars kick velocities.…”
Section: Beta Decay Of the Neutron In A Magnetic Fieldmentioning
confidence: 99%
“…Esta reducción no es trivial y va más allá del objetivo de este trabajo de Tesis. Referimos al lector a [28,53] para más detalles sobre cómo realizar este límite. En lo que sigue, nos enfocamos en la asimetría del camino libre medio de neutrinos, en la figura 4.9(a), mostramos λ abs como función de la intensidad del campo magnético.…”
Section: Resultsunclassified
“…Entendemos que el acuerdo mostrado entre el modelo de BHF y el de Skyrme en el capítulo anterior, evidencia que no se justifica el intentar llevar adelante un problema numérico tan complejo.En el último punto de esta sección hacemos una comparación con otros trabajos. Comenzamos con el de S. Shinkevich y A. Studenikin[53]. Estos autores hacen un análisis similar al nuestro, usando el marco relativista en espacio libre.…”
unclassified